СТІЙКІСТЬ РОБОЧИХ РЕЖИМІВ АВТОНОМНИХ АСИНХРОННИХ ГЕНЕРАТОРІВ ІЗ САМОЗБУДЖЕННЯМ - Красношапка, Н.Д; Пушкар, М.В.; Печеник, М.В.; Головешкін , Д.О.; Кипиченко , В.B. (Інститут електродинаміки НАН України, Київ, 2024)
The paper presents the results of investigation the stability conditions of self-excited induction generators. A mathematical model of the generating system with an analytical description of the dependence of the magnetization inductance on the current is used. It allows to avoid the iterative procedure and to scale the dependence to determine the magnetization inductance for induction machines of different types and power. The influence of the load inductance on the stability of the generating system at different rotational speeds is investigated. It is shown that an increase in the inductance value increases the system stability margins in the self-excitation zone. Also this article deals with the issues of system stability within the self-excitation zone of an induction generator at different rotational speeds depending on the value of the capacitance of self-excitation capacitors. It is depicted that at low rotational speeds there may not exist a stable operation mode in the self-excitation zone regardless of the value of the capacitance in the motor stator circuit. This method of determination the stability of the operation modes of the generation system will be useful both for the design of new systems and for the modification and adjustment of existing ones. References 9, Figures 4.